CITRUS CANKER: consequences caused on lemon productivity in the São Paulo state - Re, Tais Arieli; Rios, Marcelo; Bueno, Ana Flavia Garcia Moraes (Revista Interface Tecnológica, 2022)
The Brazilian citrus industry has a great economic importance for the country, but it is vulnerable to some pests and diseases that affect its productivity. Among these, citrus canker caused by the bacterium Xanthomonas axonopodis pv citri stands out. On alert, the Ministry of Agriculture, Livestock and Supply in circular letter nº 11/2022 informs that only qualified establishments will be able to export to the European Union due to the current situation of the disease. The related work addresses general aspects of citrus canker in lemons, which is among the diseases that most affect citrus crops. The objective of this work is to make a comprehensive survey in scientific articles, works that provide subsidies for the understanding of the disease, briefly highlighting the etiology, epidemiology, symptomatology, control and preventive methods of the disease. Currently, the disease has resulted in a large increase in the number of dissemination, thus causing a high economic loss leading to a decrease in the commercialization and profitability of the activity in the State of São Paulo and region.
Keywords: Citrus Canker; Disease; Citrus; Lemon